2016
DOI: 10.1038/nature20145
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulators signal through astrocytes to alter neural circuit activity and behaviour

Abstract: Summary Astrocytes associate with synapses throughout the brain and express receptors for neurotransmitters that can elevate intracellular calcium (Ca2+) 1-3. Astrocyte Ca2+ signaling has been proposed to modulate neural circuit activity 4, but pathways regulating these events are poorly defined and in vivo evidence linking changes in astrocyte Ca2+ to alterations in neurotransmission or behaviors is limited. Here we show Drosophila astrocytes exhibit activity-regulated Ca2+ signaling events in vivo. Tyramine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
221
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(230 citation statements)
references
References 36 publications
9
221
0
Order By: Relevance
“…Due to the slow time course of astrocytes, any immediate impact on neuronal responses would be expected to follow that time scale, or possibly create more long-term neuronal changes. This is interesting in context to a newly published study showing that astrocytic Ca 2+ signals, mediated by fly analog to neuromodulators, are directly involved in the regulation of neuronal activity and sensory-driven behaviors in drosophila flies [62]. However, direct comparisons to rodent studies should be undertaken with caution, since there are large differences in the species-specific cell and transmitter characteristics.…”
Section: Astrocytes Respond To Neuromodulatorsmentioning
confidence: 90%
“…Due to the slow time course of astrocytes, any immediate impact on neuronal responses would be expected to follow that time scale, or possibly create more long-term neuronal changes. This is interesting in context to a newly published study showing that astrocytic Ca 2+ signals, mediated by fly analog to neuromodulators, are directly involved in the regulation of neuronal activity and sensory-driven behaviors in drosophila flies [62]. However, direct comparisons to rodent studies should be undertaken with caution, since there are large differences in the species-specific cell and transmitter characteristics.…”
Section: Astrocytes Respond To Neuromodulatorsmentioning
confidence: 90%
“…Thus, both the nature and the function of astrocytic Ca 2+ -transients are likely to be distinct from that of neuronal Ca 2+ -signaling, which underlie fast synaptic transmission. In fact recent studies in Drosophila and mice have demonstrated that astrocytes respond to slow-acting neuromodulators such as norepinephrine, tyramine and octopamine with increases in intracellular calcium (Ding et al, 2013; Ma et al, 2016; Paukert et al, 2014). In Drosophila, astrocytic activation by octopamine/tyramine leads to inhibition of dopaminergic neuron firing and alterations in behavior, demonstrating an in vivo role for astrocyte calcium signaling in regulating neuronal circuit function (Ma et al, 2016).…”
Section: Astrocytes Are Integral Components Of Synapsesmentioning
confidence: 99%
“…Animal studies increasingly highlight a role for oligodendrocytes in mood regulation (99). Astrocytes also influence microcircuit function through modulation of synaptic transmission via calcium signaling, release of glutamate and purinergic neurotransmitters, and neurotransmitter recycling (100). Further, circuit connectivity depends on the formation of functional neuronal assemblies mediated by astrocytes and microglia that are similarly altered in MDD.…”
Section: Gaba and Sst Interneuron-related Microcircuit Deficits In Dementioning
confidence: 99%